2022
DOI: 10.1038/s41563-022-01285-3
|View full text |Cite|
|
Sign up to set email alerts
|

Unconventional excitonic states with phonon sidebands in layered silicon diphosphide

Abstract: Complex correlated states emerging from many-body interactions between quasiparticles (electrons, excitons and phonons) are at the core of condensed matter physics and material science. In low-dimensional materials, quantum confinement affects the electronic, and subsequently, optical properties for these correlated states. Here, by combining photoluminescence, optical reflection measurements and ab initio theoretical calculations, we demonstrate an unconventional excitonic state and its bound phonon sideband … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 58 publications
4
26
0
Order By: Relevance
“…Reduced dielectric screen- electron−hole separation or spatial delocalization, also called exciton Bohr radius) and exciton binding energy, remarkably different from those in bulk materials. 14 Increased Coulomb interaction, as discussed above, significantly hinders the dissociation of photoinduced electron−hole pairs, which in turn can severely limit the photocatalytic activity. Herein, employing GW approximation, we have not only analyzed the behavior of excitons arising in GaTeI and InTeI monolayers in the different dielectric environments but also have shown that the presence of a dielectric environment significantly reduces the exciton binding energy that is desirable for charge separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced dielectric screen- electron−hole separation or spatial delocalization, also called exciton Bohr radius) and exciton binding energy, remarkably different from those in bulk materials. 14 Increased Coulomb interaction, as discussed above, significantly hinders the dissociation of photoinduced electron−hole pairs, which in turn can severely limit the photocatalytic activity. Herein, employing GW approximation, we have not only analyzed the behavior of excitons arising in GaTeI and InTeI monolayers in the different dielectric environments but also have shown that the presence of a dielectric environment significantly reduces the exciton binding energy that is desirable for charge separation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, materials with reduced dimensionality present a new avenue for fundamental exciton physics. The ultrathin nature of 2D materials, that is, strong geometrical confinement, causes weak dielectric screening, which gives rise to increased Coulomb interaction. Reduced dielectric screening and enhanced Coulomb interaction in 2D materials can cause exciton properties, like exciton extension (bound electron–hole separation or spatial delocalization, also called exciton Bohr radius) and exciton binding energy, remarkably different from those in bulk materials . Increased Coulomb interaction, as discussed above, significantly hinders the dissociation of photoinduced electron–hole pairs, which in turn can severely limit the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of them are not competent for ultrasensitive photodetection owing to the high dark currents and low detectivity. , Recently, a new family of group IV and group V 2D layered materials such as GeP, GeAs 2 , SiAs 2 , SiP, and SiP 2 have emerged as promising candidate 2D materials for high-performance photoelectric devices. As an important member of group IV and group V 2D materials, SiP 2 is a new semiconductor with a tunable bandgap (1.99–2.25 eV), strong light absorption ability, and excellent air stability. In addition, the high carrier mobility of 1.069 × 10 5 cm 2 V –1 s –1 was theoretically predicted for monolayer SiP 2 , which can be comparable to that of graphene . Notably, the intrinsic anisotropic structure induced by zigzag phosphorus–phosphorus chains in 2D SiP 2 directly results in unique physical properties, revealing an unconventionally bright exciton with hybrid dimensionality of band-edge states . However, to date, the field effect transistor (FET) properties and gate-controlled phototransistor of SiP 2 have not yet been explored, not to mention its ultrasensitive phototransistor performance.…”
Section: Introductionmentioning
confidence: 99%
“…16 Notably, the intrinsic anisotropic structure induced by zigzag phosphorus−phosphorus chains in 2D SiP 2 directly results in unique physical properties, revealing an unconventionally bright exciton with hybrid dimensionality of band-edge states. 17 However, to date, the field effect transistor (FET) properties and gate-controlled phototransistor of SiP 2…”
Section: ■ Introductionmentioning
confidence: 99%
“…[6,7] Overall our results highlight the general importance of exciton coupling to optical phonons in this class of materials and they further suggest that also the peculiar spatial symmetry of the excitonic states and phonon modes needs to be accounted for in a proper treatment of exciton−phonon coupling. [21]…”
Section: Introductionmentioning
confidence: 99%